Hazardous alcohol consumption in non-aboriginal male inmates in New South Wales. Issue 1 (12th March 2018) - Field, Courtney
Abstract : Purpose: The purpose of this paper is to examine correlates and predictors of hazardous drinking behaviour, that may be considered evidence of generalised strain, in a sample of incarcerated non-Aboriginal males in New South Wales, Australia. Design/methodology/approach: Data were collected from 283 non-Aboriginal male inmates as part of a larger epidemiological survey of inmates in NSW undertaken in 2015 by the Justice Health and Forensic Mental Health Network. Data relating to a range of social factors were selected with reference to relevant literature and assessed with regards their predictive value for scores from the Alcohol Use Disorders Identification Test (AUDIT). To facilitate regression analysis, variables were logically organised into historical factors or adult factors. Findings: Almost all participants reported some history of alcohol consumption. Hazardous drinking was common among participants. While parental alcohol problems and adult drug use were the only correlates of AUDIT scores, parental misuse of alcohol was shown to be an important predictor of AUDIT scores in regression analysis. The role of parent gender was inconclusive. Previous incarceration as an adult, employment status, and drug use as an adult also predicted AUDIT scores. Originality/value: Alcohol abuse is common among inmates and the use of alcohol is implicated in the commission of many offences. A better understanding of its genesis may inspire novel approaches to treatment, leading to improved health outcomes for inmates.